A revolutionary history of interwar India with Professor Kama Maclean - Singh, Sukhraj (SikhArchive, 2020)
In this episode, we are joined by Professor Kama Maclean, who is a professor of South Asian History and the author of the book, “A Revolutionary History of Interwar India: Violence, Image and Text, which we will be discussing today.